Chemistry / Raymond Chang; Kenneth A Goldsby - Chang, Raymond
Features a straightforward, clear writing style and proven problem-solving strategies. This book offers a firm foundation in chemical concepts and principles while presenting a broad range of topics in a clear, concise manner.